Drivers of Regenerative Agriculture: The Next Generation of Sustainable Food Production - Csordas, Adrian (Journal of Agricultural Sciences (Belgrade), 2026)
Agriculture needs rapid and fundamental transformation to enhance its efficient and sustainable operation. Lately, Regenerative Agriculture (RA) has emerged as a comprehensive solution for the challenges of food production and climate change. Unlike the prohibition‑based approach of organic farming, RA operates as an outcome‑oriented, flexible framework focused on active ecosystem restoration. This study presents a systematic literature review based on the PRISMA guidelines to identify the key drivers of RA adoption and to provide clear recommendations for its effective introduction. The analysis highlights four categories of drivers that distinguish RA from other sustainable practices: economic (reducing input costs), ecological (restoring soil and climate resilience), social (peer networks and mentoring), and intrinsic (ecological mindset and autonomy). It is important to note that the findings primarily reflect Western farming contexts, which clarifies the generalisability of the results. To support the successful introduction of RA, policymakers and extension services should prioritise young, eco‑friendly farmers operating on a smaller scale as the primary target group, while NGOs should directly organise farm visits and provide hands‑on mentoring as necessary tools for successful adoption. Furthermore, for large‑scale operations, the implementation of financial incentives linked to carbon markets and certification schemes is essential to encourage broader uptake. According to the findings, although change is fundamentally driven by individual mindsets, the deliberate implementation of these specific suggestions can significantly aid large‑scale adoption and the development of more resilient agriculture.
Keywords: agriculture; soil; sustainability; innovation; environment; review; regenerative; farmer